Egroup Webartery: diálogo e criação - J. Andrews; R. Drake; S. Katz; T. Memmott; Marie-Anne Breeze (Galáxia, 2007)
Trata-se de uma antologia de emails do Egroup Webartery, do Canadá, no período de 12 a 26 de novembro de 2000, enfeixada sob o tema code poetry, cujo resultado, para os leitores e para os participantes, é a riqueza de informações e a criação de email poems por Ted Warnell, Alan Sondheim e Mez. Palavras-chave códigos poéticos, ciberpoesia, máquinas de linguagem, Internet, Egroup, Email Poetry Abstract The present dialogue is an anthology of emails from November 12th to 26th, 2000, under the theme of code poetry. These emails make part of the egroup Webartery, from Canada, which owner is Jim Andrews and moderator is Mez. The result of the discussion, for the readers and for the egroup participants, is the richness of information and also the creation of email poems by Ted Warnell, Alan Sondheim and Mez. Key words code poetry, cyberpoetry, language machines, Internet, Egroup, Email Poetry